The new linguistic pluralism in Apulia. The representation of the Albanian community in the local media - Montinaro, Chiara (Romanica Olomucensia, 2022)
After a brief introduction dedicated to statistics concerning the presence of foreigners in Apulia in the period 2006-2021, the paper focuses on the Albanian minority, independent of the ancient Arbëresh garrisons that have been present in the region for centuries. By analysing the databases of the main information sites in the area, it is possible to draw a picture of the Albanian presence in the region. The news is mainly related to chronicled events; an interesting aspect is that of the titles, as well as the two different types of treatment reserved for the presentation of news items in which the reference is, for example, to "accident victims" and those in which "criminals" are mentioned. The results show that, even today, this is a community that lacks an 'integrated' space concerning areas that go beyond purely criminal episodes. And the local media, as this study proves, have contributed to one of the most widespread stereotypes about Albania. Therefore, the conclusions on the subject concern the analysis of the main commonplace linked to the Albanians, namely the stereotype of the Albanian invader, which arose in the collective imagination in the 1990s, when there was a unique wave of emigration, especially because of the clamorous way in which it took place and, indeed, the way in which it was narrated by the media.
Keywords: Albanian language; linguistic minorities; Apulia; stereotypes; Albanian invasion